Cultivating Compassion: Going beyond crises - Juewei Shi; Stephen Hill; Suzanne Franzway (Peter Lang International Academic Publishers, 2023)
The massive disruptions caused by climate change, the Covid-19 Pandemic, war, and ever-rising inequalities have presented the world with challenges across social and economic life, health and education, policy, politics, and community life. Compassion is a central Buddhist value and practice but is also essential to our survival. Defined as feeling genuine concern about the suffering of others and, critically, coupled with a commitment to attempt to alleviate or prevent it. The desire and commitment to help are what differentiates compassion from similar emotions like empathy and sympathy. Compassion demands the courage to turn toward suffering with clarity and skilful means. Hence, we have the Buddhist recognition that compassion is inseparable from wisdom, in the analogy of the two wings. This book is titled, Cultivating Compassion: Going Beyond Crises as it is rooted in this perspective while presenting different approaches which aim to advance our understanding of the questions and dilemmas posed by the current global crises and the cultivation of compassion.
Keywords: 300; adaptation to crises; Buddhism; community resilience; Compassion; crises; Cultivating; Franzway; Going; Hill; Juewei; Lucy; Melville; Stephen; Suzanne